A retrospective observational study on HDP gestosis score as a predictor of PIH - Sangeeta Pahwa; Simran Kakkar (New Indian Journal of OBGYN)
Objectives: To assess the association of various risk factors enclosed in HDP gestosis score with the development of pregnancy induced hypertension. Methodology: This study was done at Sri Guru Ram Das Institute of Medical sciences and Research on patients who developed PIH (Pregnancy induced hypertension) from January 2020 to December 2020. Patients were analysed according to gestosis score given by Indian gestosis association. Based on elaborate history, clinical examination and investigations gestosis score was calculated. Results: Factors that have been found to have statistical significance in the development of HDP in the terms of p value< 0.05 are maternal anemia and primigravida. There were 17 patients who developed preeclampsia and 4 patients developed eclampsia. The major risk factors in patients with eclampsia were primigravidas with mild - moderate anaemia with short duration of co - habitation. Maximum patients who developed preeclampsia and eclampsia had gestosis score of >3 but there were 2 such patients who had gestosis score of 2 but still developed eclampsia. Patients who developed PIH, 11 patients have gestosis score of <3, 39 patients have gestosis score >3. One eclamptic patient with gestosis score of 4 suffered subacute intracranial haemorrhage and 1 preeclamptic patient with gestosis score 5 developed post partum cardiomyopathy. Conclusion: Adolescent primigravidas are more prone for eclampsia, the severe form of disease. Avoiding early marriage and explaining need for contraception to this group can reduce adolescent pregnancies and its dreaded complications. Gestosis score can be used as an effective predictor of PIH, as it is simple and costeffective.